Efficacy of citronella and cinnamon essential oils on Candida albicans biofilms - de Almeida, Leopoldina de Fátima Dantas [UNESP]; de Paula, Jacqueline Felipe; de Almeida, Rossana Vanessa Dantas; Williams, David Wynne; Hebling, Josimeri [UNESP]; Cavalcanti, Yuri Wanderley (MJS Publishing, Medical Journals Sweden AB, 2016)
Introduction: The discovery of new antimicrobials derived from plants could aid in the management of biofilm-associated infections, including denture-induced stomatitis (DS). DS is an oral infection caused by Candida biofilms on the surfaces of poorly cleansed dentures. Effective treatment of DS requires the use of an appropriate denture cleanser and preferably one that exhibits antimicrobial properties. Objective: This study aimed to evaluate the anti-Candida and anti-biofilm efficacy of two essential plant oils from Cymbopogon winterianus (citronella) and Cinnamon cassia (cinnamon). Materials and methods: Minimum Inhibitory Concentrations (MICs) and Minimum Fungicidal Concentrations (MFCs) were determined by broth microdilution, whilst anti-biofilm activity was measured against mature (cultured for 72 h) biofilms on acrylic surfaces. Candida cell viability was assessed immediately (0 h) after treatment (T0) and 48 h after biofilm re-growth (T48). Biofilm structure was determined using Scanning Electron Microscopy (SEM) at T0 and T48. Results: The respective MICs of cinnamon and citronella oils were 65 and 250 μg/ml and these were also the MFC values. For anti-biofilm efficacy, both oils significantly (p < 0.05) reduced the number of viable micro-organisms and accumulation of biofilms at T0. However, at T48, there was no difference between treated and untreated biofilms. Conclusions: It is concluded that citronella and cinnamon essential oils have potential for daily anti-candidal denture cleansing.
Keywords: Anti-infective agents; biofilm; Candida albicans; denture stomatitis; phytotherapy